(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
This article reveals the poetic features of the work of the outstanding Russian classic I. S. Turgenev in his works. The distinctive features of the characters of the main characters of his works are described. The author analyzes his contribution to the development of Russian literature, as well as the peculiarity of the perception of stories by the modern reader. Poetic features are: genre form, compositional form, features of the author’s position.